Difference Between Recovery After Meals With A Direct Time Gap And 15 Minutes After High-Intensity Exercise - Al Taris, Syarafi; Samodra, Y. Touvan Juni; Custodio, Joselito M. (Indonesian Journal of Sport, Health and Physical Education Science, 2025)
This study aims to determine the difference in the pulse rate of recovery after meals with a time gap between directly and 15 minutes after high-intensity exercise by knowing the break after. This study was in the form of an experiment using a research sample of 16 people, which was divided into 2 groups. In group 1 there were 9 people playing futsal, immediately after finishing eating. Group 2 consists of 7 people, playing 15 minutes after eating. Everyone eats together in the same portion. Pulse pulse is measured before playing, after sports (futsal) and 5 times every count for 10 seconds. The data was analyzed descriptively with the help of IBM SPSS Statistic 22 software. Based on the results of the direct group and 15 minutes, the average mean results of the direct group were 126.13 per minute and the 15 minutes group was 128. So doing strenuous activities immediately after eating is not recommended because of the risk of injury.